Integration Dematel and ANP for The Supplier Selection in The Textile Industry: A Case Study - Dana Marsetiya Utama; Bianca Maharani; Ikhlasul Amallynda (Jurnal Ilmiah Teknik Industri, 2021)
Currently, companies are required to improve supply chain performance. One of the main problems in the supply chain is the proper supplier selection. Supplier selection has an essential role in improving supply chain management performance. Supplier selection requires the proper criteria. However, the relationship between criteria is rarely considered in the selection of suppliers in the textile industry. This study tries to propose integrating the Decision Making Trial and Evaluation Laboratory (DEMATEL) and the Analytic Network Process (ANP) for supplier selection in the textile industry. Both methods are multi-criteria decision making (MCDM) tools DEMATEL is used to assess the relationship between criteria. Furthermore, ANP is used to evaluate and weigh the importance of criteria and suppliers. A case study was carried out in a textile company located in Indonesia. The results show that this procedure can identify the relationship and effect of each criterion. The results show that the product price criteria are the criteria that have the most significant weight. The criteria for conformity to specifications and consistency of quality are in second and third place. Finally, suppliers are selected based on weight assessment on each criterion by ANP.